Psychometric assessment of patients with chronic diseases in primary health care: a cross-sectional study (Research, Society and Development, 2022)
The occurrence of chronic diseases has increased among the population, its description is based on permanence, presence of residual disability, non-reversible pathological change in the body system, need for special patient training for rehabilitation and prediction of a long supervision period, observation and care. In Brazil, according to the Survey of Risk Factors and Protection for Chronic Diseases by Telephone Survey, the prevalence of self-reported hypertension went from 22.6% in 2006 to 24.3% in 2017. In primary health care chronic diseases, especially Arterial Hypertension and Diabetes Mellitus can be treated in a new health paradigm, leaving aside the individualistic model. The role of the physiotherapist in the rehabilitation and prevention of these diseases, gains great space in which their functions can be work with groups, obtaining strategy to meet a great demand and motivate the interaction and continuity of treatment. The objective of the research was to evaluate and compare resilience and life satisfaction in patients with chronic diseases who underwent physical therapy exercises with those who did not. Cross-sectional, exploratory, qualitative and quantitative study. Thirty patients between 40 and 70 years old participated in the research. The instruments used were the Life Satisfaction Scale and Resilience Questionnaire. The results and conclusion of the research showed that patients who underwent physical therapy exercises had a slight improvement in resilience and life satisfaction compared to those who did not perform physical therapy exercises.